2021
DOI: 10.1093/plphys/kiaa093
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin signaling mediates lateral root inhibition in response to K+-deprivation

Abstract: The potassium ion (K+) is vital for plant growth and development, and K+-deprivation leads to reduced crop yields. Here we describe phenotypic, transcriptomic, and mutant analyses to investigate the signaling mechanisms mediating root architectural changes in Arabidopsis (Arabidopsis thaliana) Columbia. We showed effects on root architecture are mediated through a reduction in cell division in the lateral root (LR) meristems, the rate of LR initiation is reduced but LR density is unaffected, and primary root g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 99 publications
1
23
0
Order By: Relevance
“…Root growth is determined by the balance between cell division and cell elongation [15]. To study the role of Fe in the growth and development of the root system, we observed the cell size of the meristematic zone and elongation zone in the root system grown under normal or low Fe stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Root growth is determined by the balance between cell division and cell elongation [15]. To study the role of Fe in the growth and development of the root system, we observed the cell size of the meristematic zone and elongation zone in the root system grown under normal or low Fe stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The meristem size was calculated as the area where isodiametric cells extend from the quiescent center (QC) to the cell, which was twice the length of the immediately preceding cell [16]. The boundary of the transition zone is different in each cell type, so in all the analyses performed here, the cortical cell le was used to de ne the boundary [15]. Our results showed that compared with the control, the number of cells in the meristematic zone of the root system under Fe-de cient condition was signi cantly reduced, and the length of the cells in the elongation zone was signi cantly shorter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pleiotropic K signaling beneficial under low K conditions lead to wasteful transcriptional resources during high K + conditions in A. thaliana and leads to futile activation of multiple hormone signaling pathways. K serves as a key signaling molecule for hormonal regulation required for developmental processes, biotic stress signaling, and abiotic stress signaling (Zhang et al, 2014; Hauser et al, 2017; Shabala, 2017; Hughes et al, 2020; Hetherington et al, 2021). Plants constantly sense and adjust growth and development based on nutrient availability, and in the context of K availability, all canonical mechanisms described for hormone-dependent growth modifications that involve sensing K + are based on sensing external K + at low or growth favorable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotropic K signaling beneficial under low K conditions lead to wasteful transcriptional resources during high K + conditions in A. thaliana and leads to futile activation of multiple hormone signaling pathways. K serves as a key signaling molecule for hormonal regulation required for developmental processes, biotic stress signaling, and abiotic stress signaling (Zhang et al, 2014;Hauser et al, 2017;Shabala, 2017;Hughes et al, 2020;Hetherington et al, 2021).…”
Section: Efficient Transcriptional Resource Allocation Vs Transcriptional Mismanagementmentioning
confidence: 99%
“…In turn, auxin homeostasis under Pi starvation entails the induction of DAO1 that leads to IAA oxidation and balances physiologically active IAA levels (Mellor et al, 2016;Bhosale et al, 2018). Interestingly, K and S deficiencies appear to downregulate both the IPyA and IAOx pathways to lower auxin accumulation, as the expression of YUC8, CYP79B2, and CYP79B3 in roots is significantly downregulated by K starvation (Hetherington et al, 2021), and that of YUC2/3/9 and CYP79B2 by S deficiency (Zhao et al, 2014).…”
Section: Nutrient-dependent Regulation Of Phytohormone Biosynthesis A...mentioning
confidence: 99%